The Larger the Better? The Role of Interest-Group Size in Legislative Lobbying - Maik T. Schneider (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
We develop a model of legislative lobbying where policy proposals are endogenous. We show that a policy proposer with preferences tilted towards one lobby may be induced by an increase in that interest group's size to propose policies geared towards the opposing lobby. Hence, a larger lobby size can have adverse effects on policy outcomes for this same lobby. This provides another rationale as to why some interests do not organize. Moreover, we find that a second-mover advantage in Groseclose and Snyder (1996)-type lobbying models with exogenous policy proposals can turn into a second-mover disadvantage when the proposal is endogenous.
Keywords: D72; P16; 330; legislative lobbying; vote buying; legislatures; interest groups; political economy; Gesetzgebung; Interessenpolitik; Abstimmungsregel; Neue politische Ökonomie; Theorie